Magnetic field promoted irreversible process of water based nanocomposites with heat and mass transfer flow - Noor Saeed Khan (Nature Portfolio, 2021)
Abstract Analytical analysis of two-dimensional, magnetohydrodynamic, heat and mass transfer flow of hybrid nanofluid incorporating Hall and ion-slip effects and viscous dissipation in the presence of homogeneous-heterogeneous chemical reactions and entropy generation is performed. The governing equations are modified with the help of similarity variables. The reduced resulting nonlinear coupled ordinary differential equations are solved with the help of homotopy analysis method. The effects of all the physical parameters are demonstrated graphically through a detailed analysis. The main outcome of the study is the use of applied strong magnetic field which generates the cross flow of hybrid nanofluid along the z-axis. The numerical comparison to the existing published literature is also provided.